Interactive methods aimed at improving the quality of creativity of students studying in the field of agricultural education (Texas Journal of Agriculture and Biological Sciences, 2024)
In an era where traditional pedagogical approaches often fail to engage students meaningfully, a paradigm shift towards interactive methods has emerged as a vital strategy in fostering creativity, particularly within agricultural education. This educational sector faces unique challenges, including the need to innovate sustainable practices amidst a rapidly changing global landscape. Traditional lectures and rote memorization rarely cultivate the adaptive thinking required for successful problem-solving in agricultural contexts. By integrating interactive techniques, such as collaborative projects, experiential learning, and technologyenhanced simulations, educators can create immersive learning environments that encourage students to explore, experiment, and apply their knowledge in real-world scenarios. This paper will explore the impacts of such methods on student creativity, drawing on theoretical frameworks and empirical research that illuminate the relationship between interactive learning and creative development in agricultural education, ultimately advocating for their incorporation as a standard practice in curricula